Mexican Immigration to the United States After NAFTA - Heppel, Monica L.; Torres, Luis R. (Tufts Archival Research Center, 2005)
Volume 20, Issue 2. Summer/Fall Migration between Mexico and the United States affects and is affected by political and economic conditions in both countries. The interdependent causes of this migration must be recognized and cooperation between the two countries must be increased in order to properly manage legal and illegal migration.